Advances in the knowledge and therapeutics of schizophrenia, major depression disorder, and bipolar disorder from human brain organoid research - Villanueva, Rosa (Frontiers in Psychiatry, 2023)
Tridimensional cultures of human induced pluripotent cells (iPSCs) experimentally directed to neural differentiation, termed "brain organoids" are now employed as an in vitro assay that recapitulates early developmental stages of nervous tissue differentiation. Technical progress in culture methodology enabled the generation of regionally specialized organoids with structural and neurochemical characters of distinct encephalic regions. The technical process of organoid elaboration is undergoing progressively implementation, but current robustness of the assay has attracted the attention of psychiatric research to substitute/complement animal experimentation for analyzing the pathophysiology of psychiatric disorders. Numerous morphological, structural, molecular and functional insights of psychiatric disorders have been uncovered by comparing brain organoids made with iPSCs obtained from control healthy subjects and psychiatric patients. Brain organoids were also employed for analyzing the response to conventional treatments, to search for new drugs, and to anticipate the therapeutic response of individual patients in a personalized manner. In this review, we gather data obtained by studying cerebral organoids made from iPSCs of patients of the three most frequent serious psychiatric disorders: Schizophrenia; Major Depression Disorder; and, Bipolar Disorder. Among the data obtained in these studies, we emphasize: i) that the origin of these pathologies takes place in the stages of embryonic development; ii) the existence of shared molecular pathogenic aspects among patients of the three distinct disorders; iii) the occurrence of molecular differences between patients bearing the same disorder; and, iv) that functional alterations can be activated or aggravated by environmental signals in patients bearing genetic risk for these disorders.